Charging control strategies for lithium‐ion battery packs: Review and recent developments. Issue 5 (26th November 2021) - Ghaeminezhad, Nourallah; Monfared, Mohammad
Abstract: The expanding use of lithium‐ion batteries in electric vehicles and other industries has accelerated the need for new efficient charging strategies to enhance the speed and reliability of the charging process without decaying battery performance indices. Numerous attempts have been conducted to establish optimal charging techniques for commercial lithium‐ion batteries during the last decade. However, a few of them are devoted to the comprehensive analysis and comparison of the charging techniques from the control‐oriented perspective for a battery pack. To fill this gap, a review of the most up‐to‐date charging control methods applied to the lithium‐ion battery packs is conducted in this paper. They are broadly classified as non‐feedback‐based, feedback‐based, and intelligent charging methods. Finally, the paper concludes with a comprehensive discussion of the strengths and weaknesses of the reviewed techniques.